Promoting Student Engagement and Oral Proficiency in English Through the Implementation of Task-Based Learning(TBL) (2024)
ABSTRACT: This action research project explored the impact of implementing a Task-Based Learning (TBL) approach to foster oral proficiency and engagement in English among 11th-grade students in a public school in Medellín, Colombia. Data collection instruments included research journals, student surveys, classroom observations, and oral presentations. The findings revealed that the TBL approach effectively increased student engagement by creating a collaborative and supportive environment. Activities aligned with real-life contexts, such as discussing future plans, significantly enhanced students' motivation and oral proficiency. While collaborative tasks promoted confidence and reduced anxiety, teacher interventions played a vital role in encouraging students to take risks and actively participate in speaking activities. Despite the improvements, the study highlighted challenges, such as disengagement during transitions or tasks with unclear instructions, emphasizing the need for well-structured activities and consistent scaffolding.